Characteristics of Mesenchymal Stem Cells Are Independent of Bone Marrow Storage Temperatures - Valentin Schrodi; Claudia Neunaber; Katrin Bundkirchen; Weikang Ye; Zhida Jiang; Maximilian Petri; Christian Krettek; Sandra Noack (Stem Cells International)
Mesenchymal stem cells play an important role in regenerative medicine due to their capability of self-renewal and multipotent differentiation. For research or clinical application, bone marrow aspirates are harvested during elective surgeries to isolate MSCs. If an immediate purification of the MSCs is not possible, the bone marrow must be stored. Therefore, the aim of this study was to investigate possible differences of stem cell characteristics regarding the self-renewal capability, the adipogenic, chondrogenic, and osteogenic differentiation, and the expression of surface antigens after different storage conditions of the bone marrow aspirates. Three groups were analysed: the first group was purified immediately after harvesting, the other two groups were processed after they were stored 18 to 24 hours at 22°C (room temperature) or at 4°C. Comparisons between the groups were performed using the Kruskal-Wallis test for nonparametric data. The final results showed no significant difference between the different storage conditions. Therefore, storage of bone marrow aspirates for 18 to 24 hours at room temperature or 4°C is possible without loss of stem cell characteristics.